تنمية صناعة األغذية الحالل في ماليزيا رؤية تأصيلية فقهية - Awang, Abdul Bari; Suleiman, Hassan; al-'Atrabi, Muhammad Fathi (2019)
حياتو، وقدُضمنوُاهللُتعاىلُبأسبابوُ- بذاتوُالعالية- لإلنسانُحالُاستخالفوُونزولوُإىلُاألرض )إنُلكُأالُجتوعُ فيهاُوالُتعرىُوأنكُالُتظمأُفيهاُوالُتضحى(ُطوُ:118-119 ،وجعلُيفُاألرض- مبنوُوتسخَتهُ– ماُيقوت اإلنسانُوأنعاموُ)أخرجُمنهاُماءىاُومرعاىاُ(ُ)النازعات:ُ31ُ،)وقالُتعاىلُ)فلينظرُاإلنسانُإىلُطعاموُأناُصببناُ ادلاءُصباُمثُشققناُاألرضُشقاُفأنبتناُفيهاُحباُوعنباُوقضباُوزيتوناُوطلالُُوحدائقُغلباُوفاكهةُوأباُمتاعاُلكمُ وألنعامكمُ(ُ)عبسُ:ُ24-32 .ُ)وُألعليةُصناعةُالغذاءُاشتدُالتنافسُمؤخراُيفُصناعةُاألغذيةُاحلاللُسيماُبُتُ ماليزياُوبعضُالدولُاألسيويةُُكالصُتُواذلندُواليابانُفضالُعنُالدولُالعربيةُاإلسالميةُبادلشرقُالعريب. وىذهُالورقةُ تؤكدُدورُالتنميةُالتنافسيةُيفُصناعةُاألغذيةُاحلاللُمنُخاللُالضوابطُالشرعيةُاإلسالميةُيفُماليزياُخاصةُوبُتُ غَتىاُمنُدولُالعامل. الكلمات االفتتاحية: تنمية- صناعةُ– الغذاء- احلالل- فقهية Abstract: Food -is one of the fundamental human needs. We need to live our life to the best expectation. The body needs calories and a variety of nutrients including protein, fat and carbohydrates every day to grow functions and repairs. Without food the body begins to atrophy, that is why God made on earth what sustains man and his cattle. Recently there is a strong competition -in halal food –industry, particularly between Malaysia and some of its neighbours such as China, India and Japan as well as the Arab Islamic countries in the Middle East. This paper emphasizes the role of competitive development in Halal food- industry through Islamic Sharia law principles- in particular in Malaysia- and generally other countries in the world.